Graphene Oxide in a Composite with Silver Nanoparticles Reduces the Fibroblast and Endothelial Cell Cytotoxicity of an Antibacterial Nanoplatform - Mateusz Wierzbicki; Sławomir Jaworski; Ewa Sawosz; Anna Jung; Grzegorz Gielerak; Henryk Jaremek; Witold Łojkowski; Bartosz Woźniak; Leszek Stobiński; Artur Małolepszy; André Chwalibog (Nanoscale Research Letters, 2019)
Abstract Antibacterial surfaces coated with nanomaterials, including silver nanoparticles, are considered effective alternative antimicrobial agents that can be used instead of antibiotics and chemical agents. However, reports of the potential toxicity of these materials raise questions about the safety of their use in biomedical applications. The objective of this research was to reduce the human cell cytotoxicity of silver nanoparticle-coated polyurethane foils by complexing silver nanoparticles with graphene oxide. The antimicrobial activity of nanoplatforms coated with silver nanoparticles, graphene oxide and the composite of silver nanoparticles and graphene oxide was assessed with Salmonella enteritidis. Cytotoxicity was analysed by an analysis of the viability and morphology of human fibroblasts, human umbilical vein endothelial cells (HUVECs) and chicken embryo chorioallantoic membrane. Additionally, the synthesis level of inflammatory proteins was examined for fibroblasts cultured on different nanoplatforms. The nanoplatform coated with the silver nanoparticles and graphene oxide composite showed strongest antibacterial properties, although nanoplatforms coated with only silver nanoparticles or graphene oxide also resulted in decreased S. enteritidis growth. Furthermore, a nanoplatform coated with silver nanoparticles and graphene oxide composite showed limited immunological stimulation and significantly reduced cytotoxicity towards fibroblasts, HUVECs and chicken embryo chorioallantoic membrane in comparison to the nanoplatform coated only with silver nanoparticles, due to the higher stability of the nanomaterials in the nanocomposite.